VIBRATION PERFORMANCE ENGINEERING OPTIMIZATION FOR INTERNAL COMBUSTION FORKLIFT TRUCK STEERING SYSTEM BASED ON UNIFORM DESIGN - LIU XianGui; LIU ShiBin; BI ChengYa; LI YingXin (Jixie qiangdu)
The modal analysis of steering system was made because of the excessive vibration of a certain forklift truck when the engine at medium and low speed conditions at first in this paper. The vibration optimum design was put forward to reduce the vibration of steering wheel by the method of Uniform Design. the test results show that the stiffness of improved steering system is increased and the vibration is decreased obviously on the basis of the invariability of costs,especially when the engine at low speed,the acceleration of vibration on direction x,y,z are reduced 83. 8%,90. 3%,83. 7% respectively. The optimum method provides references for the optimum design of body and frame type structures.